(untitled) (Mongolian Journal of Geography and Geoecology, 2025)
It is essential that any investigation of regime changes be grounded in long-term observational measurements and data. Ice transportation on Lake Khuvsgul plays a vital role in the socio-economic life of the surrounding region. A critical factor for ensuring the safety of ice transportation is the load-bearing strength of the ice. Accordingly, this study is designed to characterize ice phenology and dynamics over the 2003–2024 period using eight-day interval datasets, with ice volume as the principal parameter. In this study, we used MODIS satellite surface‐temperature products to estimate ice‐volume parameters via the Weinberg equation. Threshold values for the ice‐volume parameter were established using Youden’s method, based on the load-bearing strength of the ice. Threshold value distinguishing young or melting ice from growing ice were established at 1089.655 m³ t⁻¹ and 1090.015 m³ t⁻¹. The onset of ice formation occurs when the ice‐surface temperature drops below 0 °C, and melting initiates once it rises above 0 °C. This underscores the exceptional purity of Lake Khuvsgul’s ice.